GE_GERICHTE C/22664/2015 vom 3. August 2016 - GE Cour de justice (2016)
MAINLEVÉE PROVISOIRE; RECONNAISSANCE DE DETTE; BAIL À LOYER; LOYER INITIAL; FORMULE OFFICIELLE; VICE DE FORME | LP.82; CO.253; CO.270.2